Pengaruh Suhu dan Lama Pemeraman Buah Mengkudu (Morinda citrifolia L.) terhadap Produksi Sari Buah - Pertamawati Kartakusumah; Wahono Sumaryono; Defirst Ramadanty (JURNAL ILMU KEFARMASIAN INDONESIA, 2004)
The influence of temperature and time on ripening of Noni fruits (Morinda citrifolia L.) for the production of Noni juice was determined using mature, but unripe Noni fruits. The design of this experiment was a split-plot. The ripening times used as the main plot were 1, 2 or 3 months, and the ripening temperatures used as the sub-plot were 30°C, 40°C, and 50°C. The results showed that the difference of Noni juice properties at 50°C as ripening temperature during 1, 2 or 3 month were not significant, as were those at 40°C during 2 and 3 months. The concentration of antraquinon increases with the ripening time of Noni fruits.